Media + environment (University of California Press, 2019)
"Media+Environment is an open access, online, peer-reviewed journal of transnational and interdisciplinary ecomedia research. The journal seeks to foster dialogue within a fast-growing global community of researchers and creators working to understand and address the myriad ways that media and environments affect, inhabit, and constitute one another."
Keywords: Mass media and the environment : Periodicals; Ecology : Periodicals; Ecology; Mass media and the environment